Modeling and Simulation in Industrial Engineering - Ram, Mangey; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes the latest research developments in modeling and simulation in industrial engineering. Topics such as decision and performance analysis and industrial control systems are described. Case studies in industry and services as well as engineering economy and cost estimation are also covered.
Keywords: Industrial Management; Manufactures; Computer simulation; Production management; Industrial Management; Machines, Tools, Processes; Computer Modelling; Operations Management